The impact of perceived risk towards customers' attitude in online shopping - Lu, Man Hong; Mohamad, Muhammad Salyhyn; Md Yusoff, Nur E'zzati; Sazali, Nur Fatin (2015)
Past researchers found there is significant relationship between customers' perceived risks, customers' attitude and online purchase intention. Besides that, many past studies only investigated the impact of perceived risk and customers' attitude towards online shopping intention. Therefore, this study shown the impact of perceived risks towards customers' attitude in online shopping. Hence, the purpose of our research is to identify the elements of perceived risks and most influential type of perceived risk towards customers' attitude in online shopping. Four independent variables such as product risk, financial risk, non-delivery risk and psychological risk are selected for two different tables. For this quantitative research, we choose 200 people to conduct questionnaire survey. For this quantitative research, we choose 200 people to conduct questionnaire survey. Those respondents are selected by using convenience sampling method at Pengkalan Chepa, Kelantan, Malaysia. Based on data collected from our questionnaire survey, different SPSS analysis such as reliability, correlation and regression analysis were carried out to evaluate which of perceived risks influence towards customers' attitude in Malaysia e-commerce such as Zalora.com. As a result, participant factors has the greatest impact on customers' attitude followed by product risk, financial risk and non-delivery risk. However, psychological risk has negative impact on customers' attitude in online shopping. Therefore, the result from our research are applicable for e-commerce include Zalora.com